Pengaruh Lingkungan Kerja dan Stres Kerja Terhadap Kinerja Pegawai Sekretariat Dewan Perwakilan Rakyat Daerah Provinsi Sulawesi Selatan - Resbiana Angelina Lipat; Nisma Iriani (Department of Economics Education, Faculty of Economics, Universitas Negeri Makassar, 2021)
This study aims to examine and analyze the Effect of Work Environment and Work Stress on Employee Performance of the Secretariat of the Regional Representative Council of South Sulawesi Province. Data collection uses primary data obtained from 100 respondents from the Secretariat of the Regional Representatives Council of South Sulawesi Province. The test results from these data have been tested classic assumptions in the form of tests of normality assumptions, multicollinearity assumptions, and heteroscedasticity. The method of data analysis uses multiple linear regression techniques. The test results show that (1) the work environment has a significant positive effect on the performance of the staff of the Secretariat of the Regional Representative Council of South Sulawesi Province (2) work stress has no significant effect on the performance of the staff of the Secretariat of the Regional Representative Office of the South Sulawesi Province. (3) Work environment and work stress simultaneously have a significant positive effect on employee performance at the Regional Secretariat of the South Sulawesi Province.